The physiological response during optogenetic-based cardiac pacing in awake freely moving mice - Kaminosono, Jun; Kambe, Yuki; Tanimoto, Akihide; Kuwaki, Tomoyuki; Yamashita, Akira (Frontiers in Physiology, 2023)
There are several methods to control a heart rate, such as electrical stimulation and drug administration. However, these methods may be invasive or affect other organs. Recently, an optogenetic-based cardiac pacing method has enabled us to stimulate the cardiac muscle in non-contact. In many previous studies, the pacing was applied ex vivo or in anesthetized animals. Therefore, the physiologic response of animals during optogenetic pacing remains unclear. Here, we established a method of optogenetic-based cardiac pacing in awake, freely moving mice and simultaneously measured electrocardiogram, blood pressure, and respiration. As a result, light-induced myocardial contraction produces blood flow and indirectly affects the respiration rhythm. Additionally, light illumination enabled heart rate recovery in bradycardic mice. These findings may be employed for further research that relates a heartbeat state to animal behavior. Together, this method may drive the development of less invasive pacemakers without pacing leads.